2010
DOI: 10.2174/1874325001004010022
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Operatively Treated Acute Knee Dislocations

Abstract: Knee dislocation is a complex and rare injury often presenting in the context of high velocity trauma. The aim of this study is to establish the subjective outcomes of surgically treated knee dislocations. A total of 20 knees dislocations treated by open repair were reviewed. Their progress and outcomes were assessed by using a modified Lysholm score questionnaire. Data was obtained on patient demographics, details of injury, investigation, treatment, rehabilitation, 24 months objective outcome and subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 31 publications
2
14
1
Order By: Relevance
“…Our data demonstrated that male patients were more likely to sustain a knee dislocation than female patients. This increased risk of dislocations in males has been previously reported, with most case studies exhibiting a male-to-female patient ratio of 4:1 or higher [6,23,27]. However, while our data demonstrated a statistically significant increase in knee dislocations in males, this increase was slight and we found a male-to-female patient ratio of nearly 1:1.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our data demonstrated that male patients were more likely to sustain a knee dislocation than female patients. This increased risk of dislocations in males has been previously reported, with most case studies exhibiting a male-to-female patient ratio of 4:1 or higher [6,23,27]. However, while our data demonstrated a statistically significant increase in knee dislocations in males, this increase was slight and we found a male-to-female patient ratio of nearly 1:1.…”
Section: Discussionsupporting
confidence: 60%
“…Owing to the highenergy nature of knee dislocation injuries, they occur more frequently in younger and more active patient populations. The mean age of patients with knee dislocations typically reported in other studies ranges between 29 and 37 years [6,23,27]. We found a mean patient age of 35 years and a statistically significant inverse correlation between patient age and risk for dislocation.…”
Section: Discussionsupporting
confidence: 60%
“…Specific treatment depends on the exact nature of the injury, systemic status of the patient, and presence of concomitant injuries [15]. It is difficult to draw definitive conclusions in regards to outcomes following knee dislocations because of the relative rarity of the injury and the variability of the specific injury pattern, operative technique, graft selection, and rehabilitation protocol [20]. Patients who sustain a knee dislocation have decreased range of motion, increased instability, greater pain, and lower functional outcome scores compared with uninjured agematched controls.…”
Section: Commentarymentioning
confidence: 99%
“…Until recently, there was debate as to whether operative management was superior to nonoperative management, and there remains debate relating to early versus delayed surgery, a single versus multistage procedure, and ligament repair versus reconstruction, to name a few [5,[51][52][53][54][55]. Regardless of the treatment, the goal is to restore knee function by providing the patient with a pain free stable joint and full range of motion.…”
Section: Radiologic Review Of Knee Dislocationmentioning
confidence: 99%
“…Likely due to rarity, incidence data are scarce and dated, with most accounts from large academic institutions citing a rate ranging from 0.28 to 5.3 knee dislocations per year and an overall incidence of 0.02-0.2% of all orthopedic injuries [1, 3,4]. Complicating the diagnosis is that knee dislocations frequently reduce spontaneously or are reduced by paramedical personnel in the field before being evaluated by a physician [5,6]. Further compounding this problem is either a missed or delayed diagnosis in the setting of polytrauma, in which a dedicated knee ligament examination may be overlooked because attention is focused on other life-threatening injuries [7].…”
mentioning
confidence: 99%